Kualitas Pelayanan Publik di Kantor Desa Plampang Kabupaten Sumbawa Provinsi Nusa Tenggara Barat - Zul Arsa Yuladi; Abdullah Qiqi Asmara (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Service quality is a vital element that must be prioritized to achieve excellence in public service delivery. It serves as the cornerstone for any institution, directly influencing public satisfaction. Such satisfaction can only be realized when services are delivered effectively, efficiently, and in alignment with the community’s needs. This study aims to assess the quality of public services at the Plampang Village Office and identify factors that hinder its enhancement in 2022. Using a descriptive method with a qualitative approach, the research explores and analyzes various phenomena, events, social activities, attitudes, beliefs, perceptions, and community perspectives, both on an individual and collective level. The findings reveal that the assurance dimension of service quality received favorable feedback from service users. However, other dimensions still exhibit notable deficiencies, such as the public’s limited awareness of service standards, the small size of service spaces, and inadequate facilities, such as computers and laptops, which often experience technical issues, leading to delays in service completion.